CRITICISMS OF THE TENTATIVE STATEMENT OF ACCOUNTING PRINCIPLES. - Dixon, Robert L.; Kerrigan, Harry D. (The Accounting Review, 1941)
Abstract The paper considers criticisms which have been advanced relative to the Tentative Statement of Accounting Principles. An analysis of accounting writings since 1936 indicates that relatively few articles have dealt exclusively with the propositions contained in the Tentative Statement, on the other hand, scarcely any expression in connection with theoretical aspects of accounting can avoid implying either agreement or lack of agreement with or more of the propositions. In considering the possible need for uniform accounting principles, one must look to the sphere of relationships between the stockholder and the corporation, since it is in this connection that the statement of principles was established. Adverse criticisms divide themselves into four classes. The first relates to alleged defects of workmanship in the formulation of the statement. The second pertains to alleged incongruities of the various parts of the whole. The third deals with the practicality of certain propositions. The final class represents differences of opinion on fundamental theses.